The Singapore Constitution: A Brief Introduction - SMU Apolitical (Institutional Knowledge at Singapore Management University, 2013)
This primer seeks to provide an easy guide to those interested in finding out more about the Singapore Constitution. The Constitution provides for the structure of the government and the roles of the judiciary and the parliament. It also secures our fundamental liberties. Hence, some basic knowledge of the Constitution is useful for every citizen. The primer starts by providing an introduction to the Singapore Constitution and explains the meaning of the concept of separation of powers among the executive, legislature and the judiciary. It also touches on the functions of the three entities, such as how laws are made in Parliament or the impact of a court decision. The primer also takes a brief look at the electoral system and the political parties in Singapore. The use of diagrams and flowcharts should aid the readers’ understanding of the subject.